Exposure to household pet cats and dogs in childhood and risk of subsequent diagnosis of schizophrenia or bipolar disorder - Yolken, Robert; Stallings, Cassie; Origoni, Andrea; Katsafanas, Emily; Sweeney, Kevin; Squire, Amalia; Dickerson, Faith (PLOS ONE, 2019)
Background Serious psychiatric disorders such as schizophrenia and bipolar disorder have been associated with environmental exposures in early life. Contact with household pets such as cats and dogs can serve as a source of environmental exposure during these time periods. Methods We investigated the relationship between exposure to a household pet cat or dog during the first 12 years of life and having a subsequent diagnosis of schizophrenia or bipolar disorder. These studies were performed in a cohort of 396 individuals with schizophrenia, 381 with bipolar disorder, and 594 controls. The hazards of developing schizophrenia or bipolar disorder associated with first exposure to a household pet cat or dog were calculated using Cox Proportional Hazard and multivariate logistic regression models including socio-demographic covariates. Results We found that exposure to a household pet dog was associated with a significantly decreased hazard of having a subsequent diagnosis of schizophrenia (Hazard Ratio .75, p < .002) Furthermore, a significant decreased relative risk of schizophrenia was detected following exposure at birth and during the first years of life. There was no significant relationship between household exposure to a pet dog and bipolar disorder. There were no significant associations between exposure to a household pet cat and subsequent risk of either a schizophrenia or bipolar disorder diagnosis. However, there were trends towards an increased risk of both disorders at defined periods of exposure. Conclusions Exposure to household pets during infancy and childhood may be associated with altered rates of development of psychiatric disorders in later life.